COX-2/PGE2/VEGF signaling promotes ERK-mediated BMSCs osteogenic differentiation under hypoxia by the paracrine action of ECs. (January 2023) - Wu, Yeke; Liu, Min; Zhou, Hongling; He, Xiang; Shi, Wei; Yuan, Qianghua; Zuo, Yuling; Li, Bin; Hu, Qiongying; Xie, Yunfei
Graphical abstract: Schematic diagram of the mechanisms involved in PGE2 - and VEGF-mediated crosstalk between ECs and BMSCs under hypoxia. (1) Hypoxia promoted cell proliferation, ALP activity, osteogenic differentiation, and ERK phosphorylation in BMSCs, while PD98059 blocked the hypoxia-induced osteogenic differentiation. (2) RAOECs COX-2, VEGF and PGE2 secretion and migration were augmented under hypoxia, while NS398 prominently impaired ECs response to hypoxia, and exogenous PGE2 partially reversed the effect of NS398. (3) ECs synthesis and release the COX-2-dependent PGE2 and VEGF, which signal in a paracrine manner to BMSCs via EP1/2 and VEGFR, triggering phosphorylation of ERK signaling and osteogenic differentiation. ECs migration and PGE2, VEGF release were significantly enhanced in ECs: BMSCs group. Moreover, NS398 (pretreated ECs) significantly lessened the PGE2, VEGF concentrations in supernatant of the co-culture system. NS398-treated ECs and AH6809/SU5416-treated BMSCs greatly impaired the co-cultured ECs-induced enhancement of BMSCs osteogenic differentiation. Highlights: Hypoxia enhances cell proliferation and ERK-mediated osteogenic differentiation in BMSCs. Hypoxia augments COX-2-dependent PGE2, VEGF release, integrin αvβ3 expression and migration of ECs. COX-2/PGE2 /VEGF signaling is involved in intercellular BMSCs: ECs communication under hypoxia. Abstract: Understanding the crosstalk between endothelial cells (ECs) and bone-marrow mesenchymal stem cells (BMSCs) in response to hypoxic environments and deciphering of the underlying mechanisms are of great relevance for better application of BMSCs in tissue engineering. Here, we demonstrated that hypoxia promoted BMSCs proliferation, colony formation, osteogenic markers expression, mineralization, and extracellular signal-regulated protein kinase (ERK) phosphorylation, and that PD98059 (ERK inhibitor) blocked hypoxia-induced osteogenic differentiation. Hypoxia enhanced ECs migration, cyclooxygenase 2 (COX-2) and integrin αv β3 expression, and prostaglandin E2 (PGE2 ), vascular endothelial growth factor (VEGF) secretion. NS398 (selective COX-2 inhibitor) and LM609 (integrin αv β3 specific inhibitor) impaired the ECs response to hypoxia, and exogenous PGE2 partially reversed the effects of NS398. BMSCs: ECs co-culture under hypoxia upregulated BMSCs osteogenesis and ERK phosphorylation, as well as ECs migration, integrin αv β3 expression, and PGE2 and VEGF secretion. NS398 (pretreated ECs) lessened PGE2, VEGF concentrations of the co-culture system. NS398-treated ECs and AH6809 (combined EP1/2 antagonist)/L-798106 (selective EP3 antagonist)/L-161982 (selective EP4 antagonist)/SU5416 [VEGF receptor (VEGFR) inhibitor]-treated BMSCs impaired the co-cultured ECs–induced enhancement of BMSCs osteogenic differentiation. In conclusion, hypoxia enhances BMSCs proliferation and ERK-mediated osteogenic differentiation, and augments the COX-2–dependent PGE2 and VEGF release, integrin αv β3 expression, and migration of ECs. COX-2/PGE2 /VEGF signaling is involved in intercellular BMSCs: ECs communication under hypoxia.